Komunikasi Visual: Strategi Geonusantara dalam Membagikan Informasi Fotografi - Mandasari, Ika; Syahminan, Syahminan; Ismail, Ismail (Communication & Social Media, 2023)
This article aims to investigate the dynamics of internal communication, communication strategies, and obstacles faced by the Geonusantara Community in conveying photography information through social media platforms such as Instagram and WhatsApp groups. This research adopts the theory of group cohesiveness, emphasizing personality traits as the foundation of group strength. The research method employed is qualitative and descriptive, with data collection techniques involving in-depth interviews, observations, and documentary studies. Respondents include the founder, chairman, central administrator, creative team, and members of the Geonusantara Community. The research findings indicate that the internal communication process and communication strategies within this community adopt a two-way communication model. Additionally, internal communication obstacles were identified, such as differences in perception and seniority attitudes among members. This study provides profound insights into the dynamics of visual communication within the Geonusantara photography community.